Tuberculosis in Otorhinolaryngology: A Case Series and Short Review of Related Data from South-Eastern Europe - Mocanu, Horia; Mocanu, Adela-Ioana (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
This study provides significant contributions to the understanding of tuberculosis in the field of otorhinolaryngology. It highlights the diagnostic challenges posed by the rare ENT manifestations of tuberculosis, which are often mistaken for more common conditions such as neoplasms or chronic infections. The manuscript effectively underscores the importance of including tuberculosis in the differential diagnosis, especially in cases where clinical presentation is typical. Worldwide, tuberculosis can infect any part of the body, however, it most frequently affects the lungs. Even while otorhinolaryngological symptoms of tuberculosis are uncommon and typically develop as a result of lung illness, they nonetheless pose a serious diagnostic difficulty. About 1% of all upper airway localizations are caused by nasopharyngeal tuberculosis, which is uncommon and most frequently manifests as adenoids. Tuberculous glossitis (oral tuberculosis) is even scarcer and may present in various clinical forms, usually mimicking a malignant neoplasm, or, less often, trauma or other infectious lesions. Oropharynx tuberculosis is usually misdiagnosed as hypertrophic chronic tonsillitis. The study presents four rare cases of ENT tuberculosis, primary adenoiditis and tonsillitis in a 13-year-old girl, a curious case of tuberculous glossitis in a 65-year-old woman, clinically diagnosed as a lingual neoplasm and two cases of tuberculous lymphadenopathy uncommonly located in the submandibular and supraclavicular regions. A comprehensive review of literature follows the case presentations. Tuberculous manifestation in the ear, nose and throat area remains a difficult diagnosis to establish, particularly because of its rarity and non-specific clinical appearance, and should be included in the differential diagnosis of pharynx lesions. An early diagnosis is essential to avoid the occurrence of complications. Tuberculous glossitis remains a difficult diagnosis to establish, particularly because of its rarity and non-specific clinical appearance, and should be included in the differential diagnosis of oral lesions. It is rarely a primary infection, and an early diagnosis is essential to avoid the occurrence of complications.